Congenital heart disease with pulmonary artery hypertension in an Asian cohort-initial report from TACHYON (TAiwan congenital heart disease associated with pulmonarY arterial hypertension) registry. (15th October 2020) - Chiu, Shuenn-Nan; Weng, Ken-Pen; Lin, Ming-Chih; Wang, Jieh-Neng; Hwang, Be-Tau; Dai, Zen-Kong; Lin, Shan-Miao; Chang, Jeng-Sheng; Lin, I-Chun; Wu, Mei-Hwan; Lu, Chun-Wei; Lin, Ming-Tai; et al.
Abstract: Background: Prospective registry studies of congenital heart disease (CHD)-associated pulmonary artery hypertension (PAH) are rare. We established a multicenter registry of CHD-PAH: the TACHYON (TAiwan Congenital Heart disease associated with pulmonarY arterial hypertension) registry. Methods: The prospective TACHYON registry was initiated in January 2016. Nine pediatric cardiology centers with 99 patients were included. Using this database, we evaluated clinical characteristics and outcomes. Results: Twelve patients with incomplete data were excluded. For the remaining 87 patients, mean age of enrollment was 37.4 (SD 18.2) years, and the male to female ratio was 60:27. PAH after defect closure accounted for 46 (52.9%) and Eisenmenger syndrome for 30 (34.5%) cases. Atrial septal defect was the most common (48.3%) disease, followed by ventricular septal defect. Mean pulmonary artery pressure was 56.7 (SD 19.4) mmHg. PAH-targeted therapy was used in 95.4% of patients. Sildenafil and bosentan were the most common drugs. After mean 23.9 months of follow-up, the 2-year Kaplan–Meier survival rate was 93.2%. According to univariate Cox regression analysis, significant risk factors included right heart failure signs, symptom progression, high-risk baseline N-terminal pro–brain natriuretic peptide (BNP)/BNP, high-risk baseline 6-min walking distance (6MWD), and high baseline hemoglobin/hematocrit level. Using the three noninvasive parameters (functional class, 6MWD, NT-pro BNP/BNP) proposed by the European Society of Cardiology, the total number of high-risk criteria predicted survival rate reliably. Conclusions: Using the TACHYON registry is feasible, but the physicians' adherences to guidelines are unsatisfactory. Midterm outcomes of PAH-target therapy are favorable and predictable using noninvasive parameters. Highlights: This is the largest multicenter registry data from Asian country for CHD-PAH. The physicians' adherence to the ESC guidelines of CHD-PAH patients is unsatisfactory. We can predict outcome noninvasively by functional class, Pro-BNP, and 6MWD. The number of high-risk parameters has higher predictive value than low risk ones.